PENERAPAN METODE STORYTELLING TERHADAP KEMAMPUAN BERBICARA DAN KEPERCAYAAN DIRI SISWA DALAM PELAJARAN BAHASA INDONESIA KELAS IV DI SEKOLAH DASAR - Charenina Tsabitha Amanda; Hania Dwitri Fadhia; Yuliani Cindiyana Putri; Destrinelli; Risdalina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the application of the storytelling method on students' speaking ability and self-confidence in learning Indonesian in class IV SDN 14/I Sungai Baung. The background of this study is based on the low ability of students to express opinions orally and lack of self-confidence when speaking in public. This study uses a classroom action approach (CAR) which is carried out in two cycles with 20 students as subjects. The data collection technique is carried out through direct observation using an assessment sheet that includes five indicators of speaking ability and five indicators of self-confidence. The results of the study showed that the storytelling method was significantly able to improve both aspects. In cycle I, there were still a number of students who were less active and not yet confident, but in cycle II there was a significant increase in aspects of pronunciation, intonation, use of gestures, and courage in speaking and actively participating. The average class score also increased from 68.75 in cycle I to 78.5 in cycle II. Based on these results, it can be concluded that the storytelling method is effective in improving students' speaking ability and self-confidence in learning Indonesian in elementary schools.